The Macedonian front 1915-1918
1 online resource (xviii, 277 pages)
Keywords: "The 'Macedonian question' has been much studied in recent years as has the political history of the period from the Balkan Wars in 1912-13 to the Treaty of Lausanne in 1923. But for a variety of reasons, connected with the political division of Greece and the involvement of outside powers, the events at and behind the Macedonian front have been side-lined. The recent commemorations of the centenary of the end of the First World War in the UK illustrate how by comparison with the enormous and moving emphasis on the western front, Macedonia has been not wholly but largely ignored. This volume illuminates this comparatively neglected period of Greek history and examines the strategic and military aspects of the war in Macedonia and the political, social, economic and cultural context of the war"--